Efficacy and safety of the newer oral hypoglycemic agents in patients with T2DM during Ramadan: A systematic review and meta-analysis - Hoda Gad (6470522) (2020)
Aims This systematic review and meta-analysis aims to evaluate the safety and efficacy of the newer glucose lowering treatments on glycemic control, weight, blood pressure and hypoglycemia in patients with T2DM during Ramadan. Methods A literature search was done in PubMed, Embase, and the Cochrane Library. Quality assessment was done using the ROBINS-I and Cochrane tools for risk of bias and analyses were performed using RevMan version 5.3. Results A total of 20 studies were included in the meta-analysis. Dipeptidyl peptidase-4 inhibitors (DPP-4i) led to a significant reduction in HbA1c (%) (SMD -0.25) and a non-significant decrease in weight (kg) (SMD -1.06) during Ramadan. Glucagon-like peptide (GLP-1) agonist therapy was associated with a significant decrease in HbA1c (%) (SMD -0.68) and a non-significant decrease in weight (kg) (SMD -2.57) and systolic blood pressure (SBP) (mmHg) (SMD -3.50) after Ramadan. Sodium-glucose co-transporter 2 inhibitor (SGLT-2i) therapy was associated with a significant decrease in HbA1c (%) (SMD -0.51) and a non-significant decrease in weight (kg) (SMD -1.41), SBP (SMD -1.10) and diastolic blood pressure (DBP) (mmHg) (SMD -2.08) after Ramadan. Conclusions This systematic review and meta-analysis shows clinical benefits with the newer glucose lowering medications in patients with T2DM who fast during Ramadan. Other Information Published in: Diabetes Research and Clinical Practice License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.diabres.2020.108562